Splenitis in 33 Dogs. (January 2017) - Ferri, F.; Zini, E.; Auriemma, E.; Castagnaro, M.; Coppola, L. M.; Peano, A.; Martella, V.; Decaro, N.; Kuhnert, P.; Ferro, S.
Splenitis is uncommonly reported in dogs. Herein, the authors describe its prevalence, clinical findings and outcomes, histologic patterns, and causes. Splenic samples of dogs diagnosed with splenitis between 2005 and 2013 were collected and stained with hematoxylin and eosin, Gram, green-Gram, Giemsa, periodic acid–Schiff, and Ziehl-Neelsen. Samples were processed for polymerase chain reaction (PCR) to detect bacteria, fungi, and protozoa ( Leishmania infantum, Hepatozoon canis ). Thirty-three of 660 splenic samples (5%) had splenitis. Clinical findings and outcomes were available in 19 dogs (58%); 49% had weakness, 33% had fever, and 84% survived. The most frequent inflammatory patterns included purulent splenitis (27%), pyogranulomatous splenitis (24%), and neutrophilic perisplenitis (15%). One dog had a putative diagnosis of primary splenitis; in 8 dogs, microorganisms were identified histologically or by PCR in the spleen without obvious comorbidities. Twenty-four dogs (73%) had concurrent diseases; a permissive role in the development of splenitis was suspected in 21 of these cases. Histologic examination identified the cause of splenitis in 10 dogs. Bacteria were identified by PCR in 23 cases, but the bacteria were confirmed histologically in only 6 of these. Leishmania was detected with PCR in 6 dogs. Leishmania was identified in 1 dog and H. canis in another histologically, but both were PCR negative. Fungi were identified in 8 spleens by PCR and in 1 by histology. This study suggests that splenitis is uncommon in dogs and is frequently associated with systemic diseases. Prognosis is favorable in most cases. Identification of bacteria, fungi, and protozoa in the spleens of affected dogs with PCR should be interpreted cautiously, because the findings are not confirmed histologically in many cases.